The contribution of some physical and physiological abilities to the accuracy of performing the front and back straight kick skills in table tennis for students of physical education and foundation - University of Sulaymaniyah (Journal of the College of Basic Education, 2022)
The study aimed to identify the contribution of some physical and physiological capacity to perform to perform some basic skills table roller for students of School of Physical Education-University of Sulaimaniyah, and used the researchers descriptive approach in a manner standard questionnaire relations on a sample of students of School physical education and sports science for the academic year 2014 -2015's ( 20) students, were identified physical and physiological capabilities and skills are under research and tests and a major study was Procedures Find confined duration period from 10.04.2015 until 04.22.2015, and after processing the results of statistical bag system (SPSS) concluded researchers that the availability of flexibility and strength muscle and the ability Allalaktekah students this will increase the accuracy of the performance of my skills front and rear straight strike the table roller for its contribution to these two skills are, either when the lack of muscular endurance and the ability Allaktekah among students, it is not relegated to the impact on the accuracy of the performance of my skills front and rear straight strike the table roller.